Evidence in peroneal nerve entrapment: A scoping review. (31st October 2021) - Oosterbos, Christophe; Decramer, Thomas; Rummens, Sofie; Weyns, Frank; Dubuisson, Annie; Ceuppens, Jeroen; Schuind, Sophie; Groen, Justus; van Loon, Johannes; Rasulic, Lukas; Lemmens, Robin; Theys, Tom
Abstract: Background and purpose: Daily management of patients with foot drop due to peroneal nerve entrapment varies between a purely conservative treatment and early surgery, with no high‐quality evidence to guide current practice. Electrodiagnostic (EDX) prognostic features and the value of imaging in establishing and supplementing the diagnosis have not been clearly established. Methods: We performed a literature search in the online databases MEDLINE, Embase, and the Cochrane Library. Of the 42 unique articles meeting the eligibility criteria, 10 discussed diagnostic performance of imaging, 11 reported EDX limits for abnormal values and/or the value of EDX in prognostication, and 26 focused on treatment outcome. Results: Studies report high sensitivity and specificity of both ultrasound (varying respectively from 47.1% to 91% and from 53% to 100%) and magnetic resonance imaging (MRI; varying respectively from 31% to 100% and from 73% to 100%). One comparative trial favoured ultrasound over MRI. Variable criteria for a conduction block (>20%–≥50) were reported. A motor conduction block and any baseline compound motor action potential response were identified as predictors of good outcome. Based predominantly on case series, the percentage of patients with good outcome ranged 0%–100% after conservative treatment and 40%−100% after neurolysis. No study compared both treatments. Conclusions: Ultrasound and MRI have good accuracy, and introducing imaging in the standard diagnostic workup should be considered. Further research should focus on the role of EDX in prognostication. No recommendation on the optimal treatment strategy of peroneal nerve entrapment can be made, warranting future randomized controlled trials. Abstract : This scoping review mainly maps all available evidence for the treatment of foot drop due to peroneal nerve entrapment and concludes that there is insufficient evidence to support either a conservative or a surgical treatment. Furthermore, diagnostic accuracy of ultrasound and magnetic resonance imaging is compared. We also summarize reported criteria for a conduction block as well as prognostic measures in electrodiagnostic studies and investigate the added value of electrodiagnostic studies in prognostication.